Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Solve for x: x/2x+3 + 2x+3/x = 184/65​

Sagot :

Answer:

x/2x+3 + 2x +3/x = 184 /65

x(2x + 3)–1 + (2x+3)x-1 = 184/65

(2x + 3)x / (2x +3)x = 184/65

2x² + 3x / 2x² + 3x = 184/65

1x= 184/64

x = 184/64

Step-by-step explanation:

Given that: {x/(2x+3)} + {(2x+3)/x} = 184/65

⇛[{(x*x) + (2x+3)(2x+3)}/{(x)(2x+3)}] = 184/65

⇛[{x² + 2x(2x+3) + 3(2x+3)}/(2x²+3x)] = 184/65

⇛[{x² + 4x² + 6x + 6x + 9}/(2x²+3x)] = 184/65

⇛[{x² + 4x² + 12x + 9}/(2x² + 3x)] = 184/65

⇛{(5x² + 12x + 9)/(2x² + 3x)} = 184/65

On applying cross multiplication then

⇛184(2x² + 3x) = 65(5x² + 12x + 9)

Multiply the number outside of the brackets with numbers and variables in the brackets on LHS and RHS.

⇛388x² + 582x = 325x² + 780x + 584

⇛388x² + 582x -325x² - 780x - 584 = 0

⇛388x²-325x² + 582x-780x - 584 = 0

⇛63x² - 198x - 584 = 0

⇛8(7x² - 22x - 65) = 0

⇛7x² - 22x - 65 = 0

Now,

This is of the form ax² + bx + c = 0, Where, a = 7, b = -22 and c = -65

Using the quadratic formula x = [{-b±√(b²-4ac)}/2a] , we get

x = [{-(-22)±√(-22)² - 4(7)(-65)}/{2(7)]

x = [{-(-22)±√(-22*-22) - 4(7)(-65)}/{2(7)]

x = [{22 ± √(484 + 1820)}/14]

x = [{22 ± √(2304)}/14]

x = {(22 ± 48)/14}

x = {(22 + 48)/14} or {(22 - 48)/14}

x = (70/14) or (-26/14)

x = 5 or x = -13/7

Therefore, x = 5 or -13/7

Answer: Hence, the value of x for the given equation is 5 or -13/7.

Please let me know if you have any other questions.